A aplicação dos complexos à geometria: em busca de um tesouro perdido do século XX. - SILVA, Caio Rafael Miranda da (2023)
This course completion work aims at an Application of Complexes to Geometry. In this regard, we initially start from the historical character and its development over time about Complex Numbers, in order to understand who were the first people who sought to understand and contribute to this fascinating part of mathematics. Then, we will approach in detail its definitions and properties, relating the algebraic concepts, in addition to paying special attention to the geometric and trigonometric aspect, since all this will help us to solve some mathematical impasses. Finally, this work seeks to solve a geometry problem, motivated by the search for a treasure.